Synthesis of Oligo(diazaphenyls). Tailor-Made Fluorescent Heteroaromatics and Pathways to Nanostructures - Gompper, Rudolf; Mair, Hans-Jürgen; Polborn, Kurt (Synthesis, 1997)
Oligoaza derivatives of biphenyl, terphenyl, quaterphenyl, quinquephenyl, sexiphenyl, septiphenyl, octiphenyl, noviphenyl, deciphenyl and dodeciphenyl and poly(pyrimidinylenephenylene) can be synthesized from readily accessible vinamidinium salts and amidines or N,N,N'-tris(trimethylsilyl)amidines. The fluorescence of these systems can be tuned over a wide spectral range by varying number and positions of N atoms. Oligo(diazaphenyls) are thermally and photochemically stable, are easier to reduce than oligophenyls, can be dissolved at any rate in strong acids and show strong blue fluorescence in solution as well as in the solid state.
Keywords: pyrimidine syntheses; nanostructures; fluorescence; redox properties; X-ray analysis